Pengaruh Dari Intensitas Modal dan Tangibility Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Asuransi dan Perbankan Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2011-2015) - M Aldy; Sany Dwita; Mayar Afriyenti (InFestasi, 2018)
This study aims to examine the influence of capital intensity and tangibility for firm financial performance. Financial performance is the dependent variable in this study that measured by ROA (Return on Asset).Independent variable in this study are capital intensity andtangibility, using the proxies of CIR (Capital Intensity Ratio)and DER (Debt to Equity Ratio). This study uses secondary data from financial statement of banking and insurances companies listed on Indonesian Stock exchange (IDX) for the period of 2011 to 2015. The purposive sampling technique was used to choose the study’s sample, resulting with 30 banking and 10 insurances companies. The data were analyzed using multipleregression to test the hypotheses formulated in this study. The results of this study show that partially,capital intensity and tangibility variablehave significant negative influence on capital structure. Whereas simultaneously, both have significant influence on financial performance. The resulted adjusted-R square, 56.6 percent, indicatesthat5.6percentof the changes in the value of the dependent variable can be explained by the changesin the values of the independent variables, namely, capital intensity and tangibilitywhile the remaining 43.4 percentchanges are explained by other variable outside the model.